Morphophysiological characterization of Bupleurum aureum in natural populations of the Republic of Tatarstan - Olga A. Timofeeva; Svetlana A. Dubrovnaya; Landysh Z. Khusnetdinova (Acta Biologica Sibirica, 2022)
We have carried out comprehensive studies of the natural populations of Bupleurum aureum under the conditions of the Republic of Tatarstan. Therefore, we used population research, morphometric, and physiological methods in this research. In addition, we studied the morphophysiological heterogeneity of the natural populations of Bupleurum aureum, the dynamics of the population size over three years in the forests of various natural zones of the Republic of Tatarstan. For all cenopopulations, a proportional contribution of aboveground biomass to the achievement of the generative sphere can be observed, even with a significant deterioration in the growth of particular plants. We noted a decrease in plant size in low illuminated and nitrogen-poor soils (1 CP). However, plants had the best indicators of raw material quality, flavonoids content in terms of rutin, as well as soluble phenolic compounds. Powerful plants were formed under optimal conditions in deciduous forests of the forest-steppe zone, but the content of flavonoids in all parts of the plants was insignificant. However, for plants in this natural zone, a higher content of tannins was recorded. Within the republic, the species was sufficiently stable, had high plasticity, and was self-renewable. However, this species needs to be preserved, so collection of its raw materials is not recommended due to the small area of forest within which Bupleurum grows. We suggested creating artificial plantings of this species with the recreation of conditions that ensure the synthesis and accumulation of various groups of phenolic compounds.